2024
DOI: 10.1186/s12951-024-02311-z
|View full text |Cite
|
Sign up to set email alerts
|

The quest for nanoparticle-powered vaccines in cancer immunotherapy

Zhe Sun,
Hui Zhao,
Li Ma
et al.

Abstract: Despite recent advancements in cancer treatment, this disease still poses a serious threat to public health. Vaccines play an important role in preventing illness by preparing the body's adaptive and innate immune responses to combat diseases. As our understanding of malignancies and their connection to the immune system improves, there has been a growing interest in priming the immune system to fight malignancies more effectively and comprehensively. One promising approach involves utilizing nanoparticle syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 387 publications
0
1
0
Order By: Relevance
“…88 One study showed that PNPs conjugated with an anti-EGFR monoclonal antibody and 5-fluorouracil (5-FU) had increased cellular uptake and increased cytotoxicity, thereby providing a good therapeutic effect on EGFR-positive colorectal cancer. 89…”
Section: Clinical Translationmentioning
confidence: 99%
“…88 One study showed that PNPs conjugated with an anti-EGFR monoclonal antibody and 5-fluorouracil (5-FU) had increased cellular uptake and increased cytotoxicity, thereby providing a good therapeutic effect on EGFR-positive colorectal cancer. 89…”
Section: Clinical Translationmentioning
confidence: 99%